(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Subcutaneous mycoses and mycetoma are chronic granulomatous infections involving the skin and subcutaneous tissues, predominantly affecting individuals in tropical and subtropical regions. These infections are associated with significant morbidity due to delayed diagnosis and progressive tissue destruction. Accurate diagnosis requires a combination of clinical evaluation, microbiological identification, and histopathological confirmation. Early recognition is essential to initiate appropriate therapy and prevent deformity and disability. Aims: To evaluate the clinical presentation, microbiological profile, and histopathological features of subcutaneous mycoses and mycetoma and to correlate these findings for accurate diagnosis and management. Materials and Methods: This prospective observational study was conducted over a period of 18 months in the Department of Dermatology at a tertiary care center, including 35 patients clinically suspected to have subcutaneous mycoses or mycetoma. Detailed history and clinical examination were performed in all cases. Specimens was collected for microbiological analysis. Histopathological examination was also carried. Data were analyzed using descriptive statistics, and clinicopathological correlation was performed. Results: Out of 35 patients, the majority belonged to the age group of 31–50 years (18; 51.4%), with a male predominance (22; 62.9%). The most common occupation was agriculture-related work (20; 57.1%), indicating increased exposure to soil and trauma. The lower extremities were the most frequently involved site (21; 60.0%). Clinically, mycetoma was observed in 14 (40.0%) cases, followed by sporotrichosis in 10 (28.6%), chromoblastomycosis in 6 (17.1%), and other subcutaneous mycoses in 5 (14.3%). Microbiological examination showed positivity in 26 (74.3%) cases, with fungal isolates identified in 22 (62.9%) and actinomycetes in 4 (11.4%) cases. Histopathology revealed characteristic features such as granulomatous inflammation, suppurative granulomas, and presence of fungal elements or grains in 30 (85.7%) cases. A strong correlation between clinical, microbiological, and histopathological findings was observed in 28 (80.0%) cases. Conclusion: Subcutaneous mycoses and mycetoma require a multimodal diagnostic approach for accurate identification and management. Clinical suspicion supported by microbiological and histopathological evaluation significantly improves diagnostic accuracy. Integrated diagnostic strategies are essential for timely initiation of appropriate therapy and better patient outcomes.